The Happy Cultural Omnivore? Exploring the Relationship between Cultural Consumption Patterns and Subjective Well-Being - Enrico Bertacchini; Valentina Bolognesi; Alessandra Venturini; Roberto Zotti (Institute of Labor Economics (IZA), 2021)
This paper proposes a novel approach to explore the relationship between cultural participation and subjective well-being. While most empirical research has considered such a connection using cultural and leisure activities individually or in additive terms, drawing from the sociological literature, we adopt cultural consumption profiles emerging from the variety and intensity of engagement in different cultural activities simultaneously. Using data from the 2012 Italian Multipurpose survey on households "Aspects of daily life", we first derive categories of cultural consumers through Latent Class Analysis and investigate how heterogeneity in cultural profiles is associated with overall life satisfaction and relevant domains (health, leisure, friendship relations, job and economic conditions). The results of our empirical analysis indicate a positive relationship between cultural participation and overall life satisfaction. Still, a more complex picture arises when considering all the statistically significant differences in life and domain satisfaction across cultural consumption patterns. These findings contribute to a better understanding of the role of cultural consumption habits on individual well-being and have implications for culture-led welfare policies.
Keywords: I31; Z11; 330; life satisfaction; subjective well-being; cultural consumption; cultural participation; cultural activities